Managing Multi-Campus Universities in Ghana: A Comparative Analysis of University for Development Studies (Uds) and Presbyterian University College, Ghana (Pucg) - Dinye, A. (University of Ghana, 2016)
This research compared and examined the management of University for Development Studies (UDS) and Presbyterian University College, Ghana (PUCG). The main objective was to compare, analyse and explain the differences and similarities in the management of the two selected public and private multi-campus universities in Ghana. To achieve the research objectives, the qualitative method and a comparative case study approach as well as an in-depth interview technique were employed for the study. In all, eight principal officers of the two universities were purposively selected and interviewed. The research findings revealed that there are no significant differences in the management structures of the two studied universities. The findings showed that both universities do not appoint senior or principal officers to manage the campuses and both universities do not also have any formula for the allocation of infrastructure. However, among other findings, it was revealed that unlike PUCG, UDS uses some percentages/ratios based formula for the allocation of funds. The study recommends the need for the appointment of senior or principal officers (Pro-Vice Chancellors (PVC) or Vice Presidents) as campus heads and place them as top management instead of lower management as found on the synthesised management structure. Finally, the study developed and proposed a standardised mathematical formula for the fair allocation of funds in the universities.
Thesis (Mphil)-University of Ghana, 2016